فاعلية الرقابة على عقود الطلب العمومي في المؤسسات التعليمية - كحي, عبد الحليم (My University, 2023)
تهدف هده الدراسة الى الوقوف على مدى فعالية الرقابة الإدارية على ابرام الطلب العمومي في المؤسسات التربوية، وذلك بالتطرق الى كيفيات ابرام الطلب العمومي بمختلف أشكاله وصوره، وفقا للمرسوم الرئاسي 15-247 المؤرخ في 16 سبتمبر 2015، يتضمن تنظيم الصفقات العمومية وتفويضات المرفق العام إلا أنه ظهرت ميدانيا العديد من الاشكاليات تم التطرق لها في هذه الدراسة. فالمؤسسات التربوية عند تلبيتها لحاجياتها تخضع لأحكام الإجراءات المكيفة التي جاء بها المرسوم الرئاسي رقم 15-247 عند ابرامها للطلب العمومي، كون أن الاعتمادات المالية الممنوحة لها بسيطة. فتناولنا ماهية المؤسسات بالإشارة الى القانونين الأساسين النموذجين للثانوية والمتوسطة واستخرجنا منه كيفيات الانشاء والإلغاء، وطبيعة المؤسسات وصلاحياتها الإدارية والمالية، ثم تناولنا بالتفصيل المصلحة المالية التي تتم فيها كل العمليات المالية والمادية والتي يرأسها العون المحاسب للمؤسسة ويقوم بكل المراحل الإدارية المتعلقة بالآمر بالصرف طبعا تحت اشراف هذا الأخير. وكذلك رسمنا خطوات لتحضير وإعداد الطلبات العمومية وفق الإجراءات المكيفة ثم كيفيات تنفيذ العقد وصولا الى نهايته سواء كانت عادية أو استثنائية (الفسخ)، وتعرفنا على دور الهيئات أو اللجان (القبلية والبعدية) المكلفة بمراقبة عملية الاعداد والمنح والتنفيذ وتحديد مهامها بالتفصيل، ثم تقدير دورها في المساهمة في حسن استغلال الاعتمادات المرصودة تحقيقا للبرامج والأهداف المسطرة، وحماية المال العام من كل مظاهر الفساد The aim of this study is to assess the effectiveness of administrative oversight over public procurement in educational institutions by examining the various forms and methods of public procurement according to Presidential Decree 15-247 dated September 16, 2015, which regulates public contracts and delegations of public facilities. However, several issues have emerged in the field that are addressed in this study. Educational institutions, when meeting their needs through public procurement, are subject to the provisions of the adapted procedures outlined in Presidential Decree No. 15-247 when engaging in public procurement, as the financial allocations granted to them are modest. We discussed the nature of educational institutions, referring to the basic model laws for secondary and middle schools, and extracted from them the procedures for establishment and dissolution, the administrative and financial powers of these institutions. We then delved into the financial department where all financial and material transactions take place, led by the institution's accountant, who oversees all administrative stages related to expenditure orders, under the supervision of the latter. We also outlined the steps for preparing and processing public procurement requests in accordance with the adapted procedures, as well as the methods for contract execution, whether they are regular or exceptional (termination). We became familiar with the roles of the bodies or committees (preliminary and post-execution) responsible for monitoring the preparation, grants, and execution processes, specifying their tasks in detail. Additionally, we appreciated their role in contributing to the efficient use of allocated funds to achieve established programs and objectives, as well as protecting public funds from any forms of corruption.
مذكرة ماستر
Keywords: الطلب العمومي، المؤسسات التربوية، الآمر بالصرف، الرقابة الإدارية .; Public Procurement, Educational Institutions, Disbursing Officer, Administrative Control.